BEEF MEAT IN ROMANIA – REALITIES AND OPPORTUNITIES TO IMPROVE SELF-SUFFICIENCY ON LONG TERM - Mariana GRODEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
From the perspective of reaching food security, for Romania, beef meat (accounting for 10% in the total meat consumption structure, in the year 2015) is important both for dietary diversity and for the complex contribution to the valorization of the country’s agricultural resources, through the export of live animals inclusively. With a 45% decrease of live weight beef production, after the accession to the EU, with a poor quality of carcasses, as 77.9% of carcasses come from slaughtering adult cattle, out of which 49.5% cows, the beef sector in Romania is not currently in the situation to best use the opportunities provided by the European Single Market. The aim of the paper is to identify new opportunities for relaunching the domestic beef meat production, through investments on the long term, having in view the support to the sector under the NRDP 2014-2020 measures, for the long-term improvement of self-sufficiency to about 90%.